Results of Necrotic Bone Removal and Replacement with Iliac Bone in the Treatment of Nontraumatic Avascular Necrosis of the Femoral Head Ficat Stage IIb and III - Vanadurongwan, Bavornrat; Vorathepputtipong, Benjapol; Harnroongroj, Thossart (Siriraj Medical Journal, 2004)
This prospective study reported a one year follow up of seven patients (8 hips) with avascular necrosis of the femoral head, Ficat stage Ilb and III. All necrotic bone at the avascular areas were removed and repleaced with iliac bone graft. The average age of the patients was 39.3 years (range 31-35). The mean modified Harris Hip Score was 52.4 (range 35-73) preoperatively, 81 (range 67-95) at six months and 59.6 (range 38-91) at one year follow up. The mean visual analogue scale was 5.8 (range 3.0-10.0) preoperatively, 3.1 (range 0.7-5.2) at six months and 5.4 (0.6-7.9) at one year follow up. Four patients (4 hips) and successful results. Three patients (4 hips) had clinical and radiographic progression. One of them required bipolar hemiarthroplasty at 11 months postoperatively. The others (3 hips) have been planned for arthroplasty. Â Â Â Removing and replacing necrotic bone with iliac bone graft is an alternative method to preserving the femoral head in the treatment of nontraumatic avascular necrosis, Ficat stage IIb and III. Initial pain relief and clinical improvement were obtained by most patients. Patient selection is considered to be one of the important factor in predicting long term outcomes.